Porous SiO2 supported CuO as a promising catalyst on the thermal decomposition of ammonium perchlorate. (30th March 2021) - Guo, Changping; Lu, Yuewen; Tian, Yuhao; Guo, Hao; Zhang, Xingquan
Abstract : Reducing the thermal decomposition temperature of ammonium perchlorate (AP) is of great significance for its application in composite solid propellants. Here, CuO/SiO2 nanocomposites were prepared using wet impregnation method with Cu (CH3 COO)2 ·H2 O as copper precursor followed by a calcination process. The structure and morphology of the prepared samples were characterized with the help of scanning electron microscopy (SEM), Xray diffraction (XRD), and Brunauer–Emmett–Teller (BET), respectively. The outcomes revealed the uniform dispersion of CuO were throughout silica aerogels to prevent agglomeration efficiently. Moreover, results from differential scanning calorimeter (DSC) showed that CuO/SiO2 nanocomposites could effectively enhance AP's thermal decomposition since they have large specific surface areas, many active reduction sites, and good adsorption capacity. As expected, the high decomposition temperature of AP was reduced from 418.7°C to 341.8°C when the amount of CuO/SiO2 nanocomposites was 4 wt%. Therefore, silica aerogels were good catalyst supports of CuO for AP's thermal decomposition. It can bring about new potential for application of new materials in high energy as AP‐based catalysts propellants which are solid in nature. Abstract : CuO/SiO2 nanocomposites are prepared using wet impregnation method with Cu(CH3 COO)2 ·H2 O as copper precursor followed by a calcination process. DSC result shows that CuO/SiO2 nanocomposites can effectively enhance the thermal decomposition of ammonium perchlorate (AP).